Retrospective examination of cannabis vs. other substance misuse: Associations with 30-day readmission and global assessment of functioning in hospitalized patients with serious mental illness - Scott D. Lane; Lokesh R. Shahani; Rodrigo Machado-Vieira; Jair C. Soares (Psychiatry Research Communications, 2024)
Substance misuse in individuals with psychiatric disorders is associated with worsening symptoms and hospitalization. The present retrospective, observational study analyzed inpatient psychiatry hospital EHR data from 2013 to 2020 (N = 12,742) in patients with co-occurring psychiatric disorders and substance misuse. Substance use was categorized as cannabis-only, alcohol-only, or illicit/poly-substance. Two outcome variables were evaluated using multiple-regression: (1) Global Assessment of Functioning (GAF) Score at admission, and (2) 30-day readmission rate. Covariates included primary Axis I disorder, living situation, Race/Ethnicity, education, sex, age, and total same-hospital readmissions (>30 days). Controlling for all covariates, the cannabis-only group had (1) significantly higher GAF score at admission (less severity) vs. both other groups; and (2) lower 30-day readmission rates vs. the illicit/poly-substance use group only. Post-hoc analyses revealed the results for the cannabis-only group vs. other drug use groups were robust, holding across all primary psychiatric diagnoses. Study limitations included lack of formal SUD diagnosis, lack of information in the EHR to quantify substance use patterns, retrospective study design, and lack of data to examine an appropriate psychiatric inpatient group free of substance misuse. Results are discussed in terms of the putative therapeutic efficacy of THC and cannabidiol on modulation of sleep, anxiety, and agitation.